Age: Does it matter for firms to perform? - Noordin, Muhammad Arafat (Human Resource Management Academic Research Society, 2014)
Most scholars agreed that firm age determines firm growth.They claimed that hazard rate will fall with time and firm survival increases with age of the firm.It is because new firms are perceived unable to achieve economies of scale and they rarely have the sufficient managerial resources and expertise.However, prior empirical studies on firm age do not provide conclusive evidence regarding its relationship with performance.Some scholars made another conflicting remarks stating that old firms are not flexible enough to make rapid adjustment, indicating barriers to innovate and make profit.Their organizational rigidities limit their growth by inhibiting change as they become harder to change over time.Older firms are also assumed to own antiquated machines, plants and equipment that limit their capability to innovate. These arguments has raised the interest for researchers to further study issues pertaining to firm age in a variety of contexts including in relation to the business development, technology and social systems.The study attempts to explore the relationship of firm age with intellectual capital, innovation capability and value production.The unit of analysis for the study is Small and Medium Enterprises operating in Malaysia.